2014
DOI: 10.1103/physrevb.90.140403
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mn-doped II-II-V semiconductors

Abstract: A recently discovered magnetic semiconductor Ba1−xKx(Zn1−yMny)2As2, with its decoupled spin and charge doping, provides a unique opportunity to elucidate the microscopic origin of the magnetic interaction and ordering in dilute magnetic semiconductors (DMS). We show that (i) the conventional density functional theory (DFT) accurately describes this material, and (ii) the magnetic interaction emerges from the competition of the short-range superexchange and a longer-range interaction mediated by the itinerant A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
64
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 41 publications
8
64
1
Order By: Relevance
“…In previous work [12], studies using the XMCD technique showed that the long-range magnetic order in (Ba 1-x K x )(Zn 1-y Mn y ) 2 As 2 is mediated by the p states of As through As 4p -Mn 3d hybridization, and that the As K-edge XMCD intensity (polarization of doped hole carriers) is strongly connected with the magnetic ordering of the bulk sample. These results support recent theoretical calculations [13] on Mn-doped II-II-V semiconductor which predict that the mediating states are primarily derived from As 4p valence band states, and that p-d hybridization between Mn 3d and As 4p orbitals plays an important role in the exchange coupling between localized spins and itinerant holes. However, the evolution of Mn 3d and As 4p states (and their hybridization) with hole doping, and its impact on exchange interactions leading to high Tc ferromagnetic ordering temperatures, are still not fully understood and await further experimental and theoretical investigations.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…In previous work [12], studies using the XMCD technique showed that the long-range magnetic order in (Ba 1-x K x )(Zn 1-y Mn y ) 2 As 2 is mediated by the p states of As through As 4p -Mn 3d hybridization, and that the As K-edge XMCD intensity (polarization of doped hole carriers) is strongly connected with the magnetic ordering of the bulk sample. These results support recent theoretical calculations [13] on Mn-doped II-II-V semiconductor which predict that the mediating states are primarily derived from As 4p valence band states, and that p-d hybridization between Mn 3d and As 4p orbitals plays an important role in the exchange coupling between localized spins and itinerant holes. However, the evolution of Mn 3d and As 4p states (and their hybridization) with hole doping, and its impact on exchange interactions leading to high Tc ferromagnetic ordering temperatures, are still not fully understood and await further experimental and theoretical investigations.…”
Section: Introductionsupporting
confidence: 89%
“…4 (c) and (d)]. We note that typical band gaps in the II-II-V materials study here are significantly smaller than those of the GaAs-based materials, with indirect gap of order ~ 0.2 eV [13].…”
Section: Resultsmentioning
confidence: 77%
“…It was a p-type DMS. Motivated by the high T c , density functional theory (DFT) calculations 10 and photoemission spectroscopy experiments 11,12 were conducted to understand the microscopic mechanism of ferromagnetism of p-type DMS (Ba,K)(Zn,Mn) 2 As 2 . By contrast, an n-type DMS, i.e., Ba(Zn,Mn,Co) 2 As 2 was recently reported in an experiment with T c ∼ 80 K. 13 In this material, electrons are doped because of the substitution of Zn with Co, and spins are generated mainly because of (Zn 2+ , Mn 2+ ) substitutions.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, as a result of 20 years heavy investigation, record T c of (Ga,Mn)As film has been boosted from the initial 75 K 1 to ∼185 K until now. 4 Very recently Mn-doped ZnAs-based DMS materials [5][6][7][8][9][10][11] emerged, providing an alternative to study on new DMS thin films possessing better properties, especially under the circumstances that preliminary evidences in the bulk reported possible T c up to 230 K. 12 In this paper we deposited and studied the properties of the Ba 1x K x (Zn 1y Mn y ) 2 As 2 (BKZMA) (x = 0.03, 0.08; y = 0.15) DMS films for the first time. Over 320 films have been studied.…”
mentioning
confidence: 99%